2020
DOI: 10.22456/1982-8918.100316
|View full text |Cite
|
Sign up to set email alerts
|

Influência Das Tecnologias Na Retenção De Sócios Em Ginásios: Revisão Sistemática

Abstract: O objetivo desta revisão sistemática é identificar a influência das redes sociais e tecnologias na retenção de clientes em ginásios. A pesquisa foi efetuada em quatro bases de dados online, de 2011 a 2019. Através do método PRISMA (MOHER et al., 2009), foram selecionados dez artigos. Os resultados evidenciaram que as redes sociais e o uso de tecnologias são fundamentais no processo de retenção. Após a análise dos dez artigos, foram também identificadas e analisadas as variáveis características pessoais dos sóc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Similarly, a problem that fitness centre managers face on a daily basis is the retention of their members. Therefore, for this sector, it is extremely important to understand the variables that affect loyalty (Ferreira Barbosa et al, 2020). Thus, the results of this study present a strong contribution for fitness centre managers, since it highlights the intention to use this app, the most valued aspects in its use and the relationship with overall customer satisfaction, leading, then, to increased loyalty.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, a problem that fitness centre managers face on a daily basis is the retention of their members. Therefore, for this sector, it is extremely important to understand the variables that affect loyalty (Ferreira Barbosa et al, 2020). Thus, the results of this study present a strong contribution for fitness centre managers, since it highlights the intention to use this app, the most valued aspects in its use and the relationship with overall customer satisfaction, leading, then, to increased loyalty.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 79%
“…There are already studies that indicate that the adherence is higher in individuals who use mobile applications (Du et al, 2016;Voth et al, 2016). Ferreira Barbosa et al (2020) found that the use of technologies influences consumer retention in fitness centres. Given the importance of retention for this sector, these companies should invest heavily on the use of technologies.…”
Section: Literature Review 21 Technological Innovationmentioning
confidence: 99%
“…Quality assessment was performed based on standardized assessment lists (Ferreira Barbosa et al, 2020;Lara-Bocanegra et al, 2021) The quality evaluation list included 5 items (A-E). Each item was rated as '2' (fully referred), '1' (moderately referred) or '0' (not referred or unclear).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…In addition, two studies identified the importance of social networks in the process of customer retention. They concluded that the social networking sites and the use of new technologies have positive influence on client retention in fitness clubs [41]. During confinement there was an increase in offering digital channels that help guided physical activity through the use of safe, simple and easy to implement programmes and applications that cover activities related to cross-fit, yoga or dance activities for the general population or for the improvement of physical and mental well-being of older adults [42].…”
Section: New Technologiesmentioning
confidence: 99%